UV–Vis spectroscopic study and DFT calculation on the solvent effect of trimethoprim in neat solvents and aqueous mixtures - Almandoz, M. C. (2014)
The solvatochromic behavior of trimethoprim (TMP) was analyzed using UV–Vis spectroscopy and DFT methods in neat and binary aqueous solvent mixtures. The effects of solvent dipolarity/polarizability and solvent–solute hydrogen bonding interactions on the absorption maxima were evaluated by means of the linear solvation energy relationship concept of Kamlet and Taft. This analysis indicated that both interactions play an important role in the position of the absorption maxima in neat solvents. The simulated absorption spectra of TMP and TMP:(solvent)n complexes in ACN and H2O using TD-DFT methods were in agreement with the experimental ones. Binary aqueous mixtures containing as co-solvents DMSO, ACN and EtOH were studied. Preferential solvation was detected as a nonideal behavior of the wavenumber curve respective to the analytical mole fraction of co-solvent in all binary systems. TMP molecules were preferentially solvated by the organic solvent over the whole composition range. Index of preferential solvation, as well as the influence of solvent parameters were calculated as a function of solvent composition.